Development of an Advanced Dynamic Microindentation System to Determine Local Viscoelastic Properties of Polymers - Ramakers-van Dorp, Esther (Polymers (Basel), 2019)
This study presents a microindentation system which allows spatially resolved local as well as bulk viscoelastic material information to be obtained within one instrument. The microindentation method was merged with dynamic mechanical analysis (DMA) for a tungsten cone indenter. Three tungsten cone indenters were investigated: tungsten electrode, tungsten electrode + 2% lanthanum, and tungsten electrode + rare earth elements. Only the tungsten electrode + 2% lanthanum indenter showed the sinusoidal response, and its geometry remained unaffected by the repeated indentations. Complex moduli obtained from dynamic microindentation for high-density polyethylene, polybutylene terephthalate, polycarbonate, and thermoplastic polyurethane are in agreement with the literature. Additionally, by implementing a specially developed x-y-stage, this study showed that dynamic microindentation with a tungsten cone indenter was an adequate method to determine spatially resolved local viscoelastic surface properties.